De-sovereignisation as an instrument of Russia’s coercive diplomacy in the context of post-Soviet de facto states. A comparative study of Moldova and Ukraine (2014–2021). - Barbieri, Jaroslava (Cranfield University, 2022)
This project examines the de-sovereignisation processes occurring in Moldova and Ukraine as a result of Russian-instigated activities in the breakaway territories of the Pridnestrovian Moldavian Republic (PMR) and the Donetsk and Luhansk Peoples’ Republics (DNR/LNR). De-sovereignisation is defined as the process(es) whereby a state selectively facilitates state- and nation-building activities that interfere with another state’s ability to exercise control and authority over portions of its territory and population. By strengthening various attributes of sovereignty and statehood in de facto states (i.e. territories having de facto yet lacking de jure sovereignty), Russia automatically weakens those of their respective parent states, thereby making them more vulnerable to its influence. With this in mind, this thesis addresses the following research questions: How does Russia’s role in supporting the viability of post-Soviet de facto states affect reintegration prospects into their parent states? How does Russia’s involvement in the DNR/LNR compare to that in the PMR? To guide empirical research, this thesis relies on a refined version of coercive diplomacy theory, which implies the use of (verbal and non-verbal) threats and incentives to instigate behavioural change in a target state to the coercer’s advantage. Thus, this project looks at how Russian state and non-state actors have been instrumentally promoting state- and nation-building activities in the PMR and the DNR/LNR with the aim to pressurise their respective parent states into complying with Russia’s shifting demands. Critically, this project provides the first comparative study of such activities, operationalised into five domains: 1) political-diplomatic; 2) economic-financial; 3) military-security; 4) educational-cultural; 5) socio-legal. At the same time, this study distances itself from the conventional way of treating political and military leaders in de facto states as mere Russian proxies deprived of independent agency. Rather, it interrogates the extent to which local state- and nation-building initiatives are coordinated with Russia’s ruling elite and examines whether these may generate policy dilemmas for Russia. There has been a tendency to emphasise the causes of Russia’s military incursions into neighbouring countries, with little empirical analysis of the long-term consequences of such incursions on the ground. By contrast, this project acknowledges the complex and ‘messy’ realities of Russia-backed de facto states and uses apparent similarities as a starting point to examine in comparative terms idiosyncratic local developments and the ensuing challenges for reintegration prospects. This study relies on case-study analysis and draws on sources such as state documents and public statements issued by the de facto authorities and the Russian leadership, local newspaper releases, videos from state-controlled media outlets as well as semi-structured interviews with officials and experts from the countries under study.
Keywords: de-sovereignisation; 'Donbas'; 'Transdniestria'; 'DSDS21'; 'DSDS21 3MT'; 'Political Science not elsewhere classified'